Revitalisasi Makna Rahmatan Lil ‘Alamin dalam Implementasi Kurikulum Merdeka Kementerian Agama - Fatah, Nasrul; Pane, Ismail; Lestari, Wira; Aisyah, Siti (Unit Pelaksana Teknis Penelitian dan Pengabdian pada Masyarakat (UPT-P4M) STAI Auliaurrasyidin Tembilahan, 2023)
This study aims to explore the meaning and ideas that want to be built in the use of the term rahmatan lil ‘alamin in the implementation of the merdeka curriculum of the Ministry of religion. Considering the implementation of the merdeka curriculum in institutions under the auspices of the Ministry of religion, Rahmatan lil ‘Alamin sets the student profile as the peak target of competence that must be achieved by learners. This study is a literature study by taking a qualitative method and then the data is analyzed with content analysis approach. This study follows the steps of tafsir maudu'i. From this study it was found that the meaning ang interpretation of the term rahmatan lil ‘alamin in the merdeka curriculum of the Ministry of religion is the practice of moderate religious values (religious moderation) which includes human values.